Comparative analysis for estimation of the height of training wall of convergent stepped spillway - Wadhai, Prafull; Ghare, Aniruddha; Deshpande, Narendra; Vasudeo, Avinash (International Journal of Engineering and Technology, 2015)
For a dam system with inadequate capacity of spillway, provision of (RCC) roller compacted concrete stepped spillways with converging training walls prove to be an appropriate alternative. Sufficient number of guidelines and literature references are available on the design of straight side walled stepped spillways. The need was felt to conduct the experiments on stepped spillways with convergent training walls, as limited literature is available. This paper presents the comparative analysis of an experimentation conducted on flow over convergent stepped spillways having 1:1 chute slope with 45o convergence angle for different step height ratios leading to different step height variations. The findings are presented in the form of expressions for the maximum depth of flow through the training walls required to accommodate the flow rate. The observed maximum depth of flow along the training walls also compared with estimated maximum height of the training wall as per the criteria available within literature and percentage variation is worked out taking into account the step height variation. Outcomes of the experimental findings are expected to be useful for assessment of height of training walls by the hydraulic design engineers involved in rehabilitation of existing dam system and also in design of the modified spillway system that is necessarily associated with convergent training walls and stepped chute.